Hybrid nanomembrane-based capacitors for the determination of the dielectric constant of semiconducting molecular ensembles. (2nd May 2018) - Petrini, Paula A; Silva, Ricardo M L; de Oliveira, Rafael F; Merces, Leandro; Bof Bufon, Carlos C
Abstract: Considerable advances in the field of molecular electronics have been achieved over the recent years. One persistent challenge, however, is the exploitation of the electronic properties of molecules fully integrated into devices. Typically, the molecular electronic properties are investigated using sophisticated techniques incompatible with a practical device technology, such as the scanning tunneling microscopy. The incorporation of molecular materials in devices is not a trivial task as the typical dimensions of electrical contacts are much larger than the molecular ones. To tackle this issue, we report on hybrid capacitors using mechanically-compliant nanomembranes to encapsulate ultrathin molecular ensembles for the investigation of molecular dielectric properties. As the prototype material, copper (II) phthalocyanine (CuPc) has been chosen as information on its dielectric constant ( k CuPc ) at the molecular scale is missing. Here, hybrid nanomembrane-based capacitors containing metallic nanomembranes, insulating Al2 O3 layers, and the CuPc molecular ensembles have been fabricated and evaluated. The Al2 O3 is used to prevent short circuits through the capacitor plates as the molecular layer is considerably thin (<30 nm). From the electrical measurements of devices with molecular layers of different thicknesses, the CuPc dielectric constant has been reliably determined ( k CuPc  = 4.5 ± 0.5). These values suggest a mild contribution of the molecular orientation on the CuPc dielectric properties. The reported nanomembrane-based capacitor is a viable strategy for the dielectric characterization of ultrathin molecular ensembles integrated into a practical, real device technology.